2014
DOI: 10.1177/1746197914520650
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality and changes in students’ expected political participation in Chile

Abstract: To what extent does social origin impact the disposition of students toward becoming politically involved in their future adult life? Using Chilean data from Civic Education Study, 1999 (N = 5688), and International Civic and Citizenship Education Study, 2009 (N = 5192), the present research analyzes, on the one hand, the impact of socioeconomic variables on attitudes toward future political participation and, on the other hand, explores to what extent the association between social origin and participation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
0
16
0
13
Order By: Relevance
“…However, there is still a long way to go to make this the norm, since in Chile, the greatest range of civic knowledge and the highest expectation of political participation is found in the country’s highest socio-economic strata (Castillo et al, 2014b; Treviño et al, 2017). This situation is not unique to Chile, and numerous studies have indicated that the level of participation of young people and their knowledge of civic issues are directly proportional to their economic level (Hooghe and Dassonville, 2013; Scholzman et al, 2012 Schulz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a long way to go to make this the norm, since in Chile, the greatest range of civic knowledge and the highest expectation of political participation is found in the country’s highest socio-economic strata (Castillo et al, 2014b; Treviño et al, 2017). This situation is not unique to Chile, and numerous studies have indicated that the level of participation of young people and their knowledge of civic issues are directly proportional to their economic level (Hooghe and Dassonville, 2013; Scholzman et al, 2012 Schulz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the researchers suggest that there is a window of opportunity for schools to make a difference in spite of SES differences. Previously, Castillo et al (2014) conducted a similar study of the influence of SES on Chilean students’ future expected political participation over time using CIVED 1999 and ICCS 2009 (authors do not indicate if data are from the Main Survey or the Latin American Module). They argue that ‘the results support the hypothesis that social origin continues to have a strong influence on students’ attitudes toward political participation’ (p. 140).…”
Section: Resultsmentioning
confidence: 99%
“…Castillo et al (2014) found that school-age children of families from lower socioeconomic status had lower expectations of voting in the future. Further, consistency between parent and child attitudes and/or behavior has been observed in several empirical studies (Gidengil et al 2016;Niemi 1968, 2015;Jennings et al 2009;Niemi and Hepburn 1995;Quintelier 2015).…”
Section: Political Outcomes Socioeconomic Status and Political Sociamentioning
confidence: 98%